2019
DOI: 10.4103/ijnmr.ijnmr_184_18
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality in Iranian hemodialysis patients: A systematic review and meta-analysis

Abstract: Background:Hemodialysis is a major therapeutic method for many chronic kidney disease patients that causes complications. One of these complications tends to be sleep disorders. This study was performed through systematic review and meta-analysis to determine the prevalence of low sleep quality in hemodialysis patients in Iran.Materials and Methods:Journal papers written in English and Persian searched from January 2000 to July 2018 were selected. The search keywords included (Prevalence OR Epidemiology) AND (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…According to the latest census data released in the China Kidney Disease Network Data Report (2), the prevalence of maintenance hemodialysis among patients with chronic renal failure in China is 402.18 per million. Hemodialysis treatment preserves the lives of patients with terminal stage renal failure but does not prevent the emotional suffering associated with chronic stress related to the disease burden, dialysis treatment, functional limitation, and fear of death (3)(4)(5)(6)(7). The incidence of emotional distress is higher in patients who received maintenance hemodialysis than in those with chronic kidney disease alone (8).…”
Section: Introductionmentioning
confidence: 99%
“…According to the latest census data released in the China Kidney Disease Network Data Report (2), the prevalence of maintenance hemodialysis among patients with chronic renal failure in China is 402.18 per million. Hemodialysis treatment preserves the lives of patients with terminal stage renal failure but does not prevent the emotional suffering associated with chronic stress related to the disease burden, dialysis treatment, functional limitation, and fear of death (3)(4)(5)(6)(7). The incidence of emotional distress is higher in patients who received maintenance hemodialysis than in those with chronic kidney disease alone (8).…”
Section: Introductionmentioning
confidence: 99%
“…Results on sleep quality were different to those reported in the literature. While only 15% of patients with reported altered sleep were found, sleep disturbance was reported at weighted mean prevalence of 44% with a range of 20 to 83% [ 12 , 25 , 26 ] in various countries. The observed difference may be due to the questionnaire used to assess the sleep quality in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that sleep disturbances were the most severe physical symptom of patients receiving haemodialysis, which further reduced their spiritual well‐being (Eslami et al., 2014 ), our result in line with this study. Mirghaed et al., ( 2019 ) conducted a systematic review of 21 studies on sleep disturbances in patients receiving haemodialysis. The study revealed that sleep disturbance is a common health issue among patients receiving haemodialysis and that 75.3% of patients receiving dialysis had poor sleep quality.…”
Section: Discussionmentioning
confidence: 99%